PENGARUH PELAKSANAAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN BERDASARKAN PERSEPSI PEMERIKSA PAJAK DAN WAJIB PAJAK (STUDI KASUS PADA KPP PRATAMA BANDUNG CICADAS) - Fajar, Catur Martian (LPPM Universitas BSI, 2013)
ABSTRACTTaxes arethe mainsource ofstate revenuein addition to revenues from oilandnon-oilsources. Thus, the taxis a source of revenue that must bestrategically managed. In thecurrenttaxationliteratureare twotermsin minimizingtaxpayerthe amount of taxpayable, thetax evasion (taxavoidance) and tax evasion (taxevasion). Therefore, the tax auditis one oflaw enforcementeffortsin order to improvetax compliance. This study aims to determine the effect of Tax Audit Execution Against Taxpayer Compliance In KPP Pratama Bandung Cicadas. The method used in this study is a quantitative method that is associative causal (cause and effect). Results of analysis based on the perception of Audit and Tax Officers. Results of the analysis based on the perception of tax inspectors produce a correlation coefficient () of 0.781, the coefficient of determination of 0.610, and the comparison with and is , which means that the implementation of significant tax audits on tax compliance body. Results of the analysis based on the perception of the taxpayer produces a correlation coefficient () of 0.840, the coefficient of determination equal to 0.705, and the results obtained from the comparison with and is , which means that the implementation of tax audits significantly influence Taxpayer compliance. Results of the analysis based on the perception of tax inspectors and taxpayers generate correlation coefficient () of 0.758, the coefficient of determination of 0.575, And comparative results with and is ,which means a significant effect on tax audit tax compliance. Based on the analysis results, it can be concluded that the implementation of the tax audit has a significant effect on the Taxpayer compliance in KPP Pratama Bandung Cicadas. Therefore, the implementation of optimal inspection needs to be done optimally to improve tax compliance. keywords: implementation of tax audit, taxpayer compliance, tax inspectors, corporatetaxpayers